European Cinema after the Wall: Screening East-West Mobility - Leen Engelen, Leen Engelen; Heuckelom, Kris Van (Rowman & Littlefield Publishers, 2013)
Since the fall of the Berlin Wall in 1989, transnational European cinema has risen, not only in terms of production but also in terms of a growing focus on multiethnic themes within the European context. This shift from national to trans-European filmmaking has been profoundly influenced by such historical developments as the collapse of the Iron Curtain and the subsequent ongoing enlargement of the European Union. In European Cinema after the Wall: Screening East–West Mobility, Leen Engelen and Kris Van Heuckelom have brought together essays that critically examine representations of post-1989 migration from the former Eastern Bloc to Western Europe, uncovering an array of common tropes and narrative devices that characterize the influences and portrayals of immigration. Featuring essays by contributors from backgrounds as divergent as film studies, Slavic and Russian studies, comparative literature, sociology, contemporary history, and communication and media studies, this volume will appeal to scholars of film, European history, and those interested in the impact of migration, diaspora, and the global flow of cinematic culture.